A hydrogenation catalyst and its preparation method and application
By using inorganic resistant oxide support, noble metal active components and carbon additives in the anthraquinone hydrogenation catalyst, and carrying out polymer coating and carbonization treatment, the problem of low stability of long-term operation activity of the catalyst is solved, and efficient anthraquinone hydrogenation reaction and long-life use of the catalyst are achieved.
Patent Information
- Application Number
- CN202110862672.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-07-29
AI Technical Summary
The existing anthraquinone hydrogenation catalysts have low activity stability during long-term operation, resulting in problems such as low catalytic efficiency, high by-products, catalyst wear and depalladium.
Inorganic resistant oxides are used as support, noble metals Pd or Rh are used as active components, and carbon is used as additives. Through polymer coating and carbonization treatment, the active components and additives of noble metals are distributed on the surface of the carrier, thereby improving the long-term operation activity of the catalyst.
It significantly improves the long-period operation activity stability of the anthraquinone hydrogenation reaction, reduces the generation of by-products, and extends the service life of the catalyst.
Smart Images

Figure 877621DEST_PATH_IMAGE002
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogenation catalyst and a preparation method and application thereof, and in particular to an anthraquinone hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide is an important chemical raw material. It can be used as an oxidant, bleaching agent, initiator and disinfectant, and is therefore widely used in the fields of textiles, papermaking, environmental protection, food processing, electronic processing, medicine and cosmetics. Hydrogen peroxide is environmentally friendly and pollution-free during use. With the increasingly stringent environmental regulations and the increasing maturity of green synthesis processes such as the HPPO method for producing propylene oxide and the cyclohexanone ammoxidation method for producing caprolactam, the demand for hydrogen peroxide is also increasing day by day.
[0003] The main methods for producing hydrogen peroxide include the anthraquinone method, isopropanol method, acid hydrolysis peroxide method, electrolytic hydrolysis method, etc., and the current mainstream method for producing hydrogen peroxide in industry is the anthraquinone method. The anthraquinone method uses anthraquinone as a raw material, dissolves it in an organic solvent to make a working solution, and then undergoes hydrogenation, oxidation, extraction and post-treatment to obtain a hydrogen peroxide product. Among them, the hydrogenation process of anthraquinone is an important link in the production of hydrogen peroxide, and the catalyst is the core of the anthraquinone hydrogenation reaction. At present, the anthraquinone hydrogenation catalyst mainly uses the precious metal Pd as the active component, and the composition and structure of the carrier are important factors affecting the performance of the catalyst.
[0004] The granular supported catalyst carrier commonly used in industry has low mass transfer / heat transfer performance in the catalyst bed during use, resulting in low effective utilization of the catalyst and unit catalyst product yield. The granular stacked fixed bed anthraquinone hydrogenation technology has problems such as low catalytic efficiency, high by-products, catalyst wear and palladium removal. In particular, excessive side reactions during the anthraquinone hydrogenation reaction lead to serious anthraquinone degradation, which increases the operating cost of the device.
[0005] Chinese patent CN103769091 discloses a hydrogenation catalyst for preparing hydrogen peroxide by anthraquinone method, which is composed of nano magnesium oxide, silicon oxide, rare earth elements, tin and active metal components. It is applied to anthraquinone hydrogenation reaction to prepare hydrogen peroxide, and has the characteristics of high hydrogenation efficiency and low anthraquinone degradation. Chinese patent CN106984308 discloses a high-stability hydrogenation catalyst for preparing hydrogen peroxide by anthraquinone method. This catalyst uses Ba and Zn as additives, which are evenly distributed in the carrier phase, and the metal active component Pd is evenly distributed on the surface of the carrier. The catalyst prepared in this way has the advantages of good hydrogenation stability, high selectivity and simple preparation process. Chinese patent CN111068787 discloses a hydrogen peroxide anthraquinone hydrogenation catalyst prepared by coating a carrier with a metal organic ligand compound. The hydrogen peroxide catalyst of this invention effectively avoids the occurrence of deep impregnation of metal active components, thereby avoiding deep hydrogenation in the process of producing hydrogen peroxide, reducing the generation of invalid anthraquinone, and improving the selectivity of the catalyst. Improving the selectivity of anthraquinone hydrogenation reaction and reducing the consumption of effective anthraquinone have become hot topics of research at home and abroad. Foreign researchers Drelinkiewicz et al. (Drelinkiewicz A, Waksmundzka-Góra A, Makowski W, et al. Pd / polyaniline (SiO2) a novel catalyst for the hydrogenation of 2-ethylanthraquinone[J]. Catalysis Communications, 2005, 6(5): 347-356.) used polyaniline-modified silica microspheres as carriers and loaded the precious metal Pd to prepare anthraquinone hydrogenation catalyst that has higher anthraquinone hydrogenation selectivity than Pd / SiO2 catalysts, but its long-term operation stability needs to be further improved. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a hydrogenation catalyst and a preparation method and application thereof. The catalyst is applied to anthraquinone hydrogenation to produce hydrogen peroxide, which can significantly improve the activity of the anthraquinone hydrogenation reaction in long-term operation.
[0007] A hydrogenation catalyst, comprising an inorganic refractory oxide as a carrier, a Group VIIIB noble metal as an active component, and carbon as a promoter, wherein the Group VIIIB noble metal active component and the promoter carbon are distributed on the surface of the inorganic refractory oxide carrier; based on the weight of the final hydrogenation catalyst, the content of the Group VIIIB noble metal active component as a single substance is 0.05% to 2%, preferably 0.2% to 0.35%, and the content of the promoter carbon is 0.05% to 5%, preferably 0.2% to 2%.
[0008] In the above catalyst, the surface layer is the area from the catalyst surface to 100 microns of the catalyst body.
[0009] In the above catalyst, the inorganic refractory oxide is selected from one or more of silicon dioxide, aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, silicon aluminum oxide, silicon magnesium oxide, and molecular sieves, preferably one of aluminum oxide and silicon dioxide. Based on the weight of the final hydrogenation catalyst, the content of the inorganic refractory oxide carrier is 90% to 99.7%, preferably 97% to 99%.
[0010] In the above catalyst, the Group VIIIB noble metal is selected from at least one of Pd, Rh and Pt, preferably at least one of Pt and Pd.
[0011] The above catalyst may further contain other auxiliary components, which are one or more of Fe, Cu, Ni, Zn, B, and P. The other auxiliary components are preferably distributed on the surface of the inorganic refractory oxide carrier. Based on the weight of the final hydrogenation catalyst, the content of the other auxiliary components is 0.2% to 3%, preferably 0.5% to 1%.
[0012] In the above catalyst, the inorganic refractory oxide carrier is a molded carrier, and the shape of the carrier can be determined according to needs, generally one of spheres, strips, and cloverleaf shapes, preferably spheres, and more preferably toothed spheres.
[0013] A method for preparing a hydrogenation catalyst comprises the following steps:
[0014] (1) selecting or preparing a shaped inorganic refractory oxide carrier, and coating the surface of the inorganic refractory oxide carrier with a high molecular polymer;
[0015] (2) introducing a Group VIIIB noble metal active component into the material obtained in step (1);
[0016] (3) The material obtained in step (2) is subjected to carbonization treatment to obtain the final hydrogenation catalyst.
[0017] In step (1) of the above method, the inorganic refractory oxide is selected from one or more of silicon dioxide, aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, silicon aluminum oxide, silicon magnesium oxide, and molecular sieves, preferably one of aluminum oxide and silicon dioxide. Based on the weight of the final hydrogenation catalyst, the content of the inorganic refractory oxide carrier is 90% to 99.7%, preferably 97% to 99%.
[0018] In step (1) of the above method, the inorganic refractory oxide carrier is a molded carrier. The shape of the carrier can be determined according to needs, and is generally one of spherical, bar-shaped, and clover-shaped. It is preferably spherical, and more preferably toothed spherical.
[0019] In step (1) of the above method, the high molecular polymer is one or more of polyaniline, polypyrrole and polythiophene.
[0020] In step (1) of the above method, the inorganic refractory oxide carrier surface-coated high molecular polymer is prepared by a polymerization reaction on the surface of the inorganic refractory oxide carrier.
[0021] In step (2) of the above method, the Group VIIIB noble metal is selected from at least one of Pd, Rh, and Pt, preferably at least one of Pt and Pd.
[0022] In step (2) of the above method, the active component of the Group VIIIB noble metal can be introduced into the material obtained in step (1) by an impregnation method, which can be equal volume impregnation, excess volume impregnation, or spray impregnation. The pH value of the impregnation solution is controlled between 2.5 and 4.5, which is conducive to the loading of the active component of the Group VIIIB noble metal on the surface of the carrier.
[0023] In step (2) of the above method, other auxiliary components can be further introduced into the material obtained in step (1), and the other auxiliary components can be one or more of Fe, Cu, Ni, Zn, B, and P, and the introduction method can be a spray impregnation method.
[0024] In step (2) of the above method, after the introduction of the Group VIIIB noble metal active component and / or other auxiliary components, a drying process may be further included, wherein the drying temperature is 80° C. to 180° C. and the drying time is 8 h to 24 h.
[0025] In step (3) of the above method, the carbonization treatment is calcination under a protective atmosphere, and the protective atmosphere is a hydrogen atmosphere, a nitrogen atmosphere or an inert gas atmosphere, preferably a hydrogen atmosphere; the calcination temperature is 400°C to 1000°C, preferably 600°C to 800°C, and the calcination time is 1h to 24h, preferably 3h to 8h.
[0026] A method for producing hydrogen peroxide by hydrogenating anthraquinone, using the catalyst prepared by the above method, wherein the reaction temperature of the hydrogenation reaction is 20°C to 100°C, the reaction pressure is 0.1MPa to 2.0MPa, and the volume space velocity is 1h -1 ~20h -1 , the gas-agent ratio is 6~500.
[0027] Compared with the prior art, the hydroprocessing catalyst of the present invention and its preparation method and application have the following advantages: during the carbonization process of the high molecular polymer in the catalyst, the overall conductivity of the catalyst is improved, and the binding force with the active metal is enhanced, thereby improving the bonding between the metal and the carrier, which is beneficial to improving the activity stability of the long-term operation of the anthraquinone hydrogenation reaction. DETAILED DESCRIPTION
[0028] The following examples and comparative examples are used to further illustrate the effects and effects of the method of the present invention, but the following examples do not limit the method of the present invention. In the following examples and comparative examples, unless otherwise specified, the raw materials used can be obtained by commercial purchase or preparation, and the percentages used are all weight percentages unless otherwise specified.
[0029] In certain specific embodiments of the present invention, a method for preparing a hydrogenation catalyst specifically includes the following contents:
[0030] (1) adding aniline to a hydrochloric acid aqueous solution at room temperature, stirring for a period of time, adding an inorganic refractory, and then adding an ammonium persulfate solution to initiate the polymerization reaction of aniline; after filtering, washing, and drying, an inorganic refractory carrier coated with polyaniline is obtained;
[0031] (2) loading a Group VIIIB noble metal on the catalyst carrier prepared in step (1) and drying the catalyst carrier; the content of the Group VIIB noble metal as an element is 0.05% to 2%, preferably 0.2% to 0.35%, based on the total weight of the final hydrogenation catalyst;
[0032] (3) Under a protective atmosphere, the catalyst in step (2) is carbonized at high temperature and then cooled to obtain a final hydrogenation catalyst.
[0033] In the above method, the molar concentration of aniline used in step (1) is 0.01 mol / L~0.5 mol / L, the concentration of the hydrochloric acid solution is 0.2 mol / L~2.5 mol / L, the molar ratio of aniline to ammonium persulfate is 1:(0.5~2.5), the amount of inorganic refractory added is 20 g / L~150 g / L, the drying temperature of the carrier obtained after the polymerization reaction is 60°C~140°C, preferably 80°C~100°C, and the drying time is 4h~12h.
[0034] In the above method, the loading method described in step (2) is an impregnation method, the pH value of the impregnation solution is adjusted between 2.5 and 4.5, the impregnation temperature is 50°C to 80°C, and the impregnation time is 1h to 5h. After the impregnation is completed, the drying temperature is 80°C to 180°C, and the drying time is 8h to 24h.
[0035] In the above method, the protective atmosphere in step (3) is a hydrogen atmosphere, a nitrogen atmosphere or an inert gas atmosphere, preferably a hydrogen atmosphere; the carbonization temperature is 600° C. to 800° C., and the carbonization time is 1 h to 24 h, preferably 3 h to 8 h.
[0036] The present invention uses a 10mL fixed bed microreactor to evaluate the performance of the catalyst in catalytic anthraquinone hydrogenation. The reaction temperature is 55°C, the reaction pressure is 0.25MPa, and the volume space velocity is 10h -1 , the gas-agent ratio is 10. The working solution composition used is: 2-ethylanthraquinone content is 140g / L, and the volume ratio of heavy aromatics to trioctyl phosphate is 7:3. Take the hydrogenated liquid after continuous operation for 200h, oxidize it with air at 50℃ for 30min, extract the oxidized liquid with deionized water for 4 times, determine the concentration of hydrogen peroxide in the extract by potassium permanganate titration, and calculate the hydrogenation efficiency.
[0037] Example 1
[0038] Prepare a 0.5 mol / L hydrochloric acid aqueous solution, add 0.03 mol / L aniline, stir until completely dissolved, then add 100 g / L toothed spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:1 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 4 hours to obtain a polyaniline-wrapped toothed spherical alumina carrier Z1.
[0039] According to the Pd content of 0.30wt% in the final catalyst, an appropriate amount of palladium chloride was weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 3.5. The carrier Z1 was immersed in the palladium chloride solution at 60°C for 4h, and then dried at 80°C for 24h. Then, under a hydrogen atmosphere, the catalyst was carbonized at 600°C for 6h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C1. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C1 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0040] Example 2
[0041] Prepare a 0.2 mol / L hydrochloric acid aqueous solution, add 0.01 mol / L aniline, stir until completely dissolved, then add 50 g / L spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:1.5 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 4 hours to obtain a polyaniline-wrapped spherical alumina carrier Z2.
[0042] According to the Pd content of 0.30wt% in the final catalyst, an appropriate amount of palladium chloride was weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 3.5. The carrier Z2 was immersed in the palladium chloride solution at 60°C for 4h, and then dried at 180°C for 8h. Then, under a nitrogen atmosphere, the catalyst was carbonized at 800°C for 8h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C2. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C2 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0043] Example 3
[0044] Prepare a 2.5 mol / L hydrochloric acid aqueous solution, add 0.5 mol / L aniline, stir until completely dissolved, then add 150 g / L toothed spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:1 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 4 hours to obtain a polyaniline-wrapped toothed spherical alumina carrier Z3.
[0045] According to the Pd content of 0.27wt% in the final catalyst, appropriate amounts of palladium chloride and zinc chloride were weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 3.0. The carrier Z3 was immersed in the palladium chloride and zinc chloride solution at 60°C for 4h, and then dried at 120°C for 12h. Then, under a hydrogen atmosphere, the catalyst was carbonized at 700°C for 8h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C3. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C3 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0046] Example 4
[0047] Prepare a 1 mol / L hydrochloric acid aqueous solution, add 0.03 mol / L aniline, stir until completely dissolved, then add 100 g / L toothed spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:2 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 6 hours to obtain a polyaniline-wrapped toothed spherical alumina carrier Z4.
[0048] According to the Pd content of 0.30wt% in the final catalyst, an appropriate amount of palladium chloride was weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 4.5. The carrier Z4 was immersed in the palladium chloride solution at 60℃ for 4h, and then dried at 80℃ for 24h. Then, under a hydrogen atmosphere, the catalyst was carbonized at 800℃ for 3h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C4. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C4 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0049] Example 5
[0050] Prepare a 0.5 mol / L hydrochloric acid aqueous solution, add 0.03 mol / L aniline, stir until completely dissolved, then add 100 g / L toothed spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:1.2 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 4 hours to obtain a polyaniline-wrapped toothed spherical alumina carrier Z5.
[0051] According to the Pd content of 0.35wt% in the final catalyst, an appropriate amount of palladium chloride was weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 3.5. The carrier Z5 was immersed in the palladium chloride solution at 60℃ for 4h, and then dried at 150℃ for 12h. Then, under a hydrogen atmosphere, the catalyst was carbonized at 700℃ for 4h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C5. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C5 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0052] Example 6
[0053] Prepare a 0.5 mol / L hydrochloric acid aqueous solution, add 0.05 mol / L aniline, stir until completely dissolved, then add 100 g / L toothed spherical alumina beads, stir, then add ammonium persulfate at a molar ratio of aniline to ammonium persulfate of 1:1 to initiate polymerization. After the reaction is completed, filter, wash, and dry at 90°C for 4 hours to obtain a polyaniline-wrapped toothed spherical alumina carrier Z6.
[0054] According to the Pd content of 0.25wt% in the final catalyst, an appropriate amount of palladium chloride was weighed to prepare an aqueous solution, and the pH of the solution was adjusted to 3.5. The carrier Z6 was immersed in the palladium chloride solution at 60°C for 4h, and then dried at 80°C for 24h. Then, under a nitrogen atmosphere, the catalyst was carbonized at 600°C for 3h to obtain a carbonized polyaniline-modified anthraquinone hydrogenation catalyst C6. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of the catalyst C6 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0055] Comparative Example 1
[0056] Take the toothed spherical alumina carrier Z1 wrapped with polyaniline prepared in Example 1, weigh an appropriate amount of palladium chloride to prepare an aqueous solution according to the Pd content of 0.30wt% in the final catalyst, and adjust the pH of the solution to 3.5. The carrier Z1 was immersed in the palladium chloride solution at 60°C for 4h, then dried at 100°C for 6h, and low-temperature calcined at 160°C for 4h to obtain catalyst E1. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of catalyst E1 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0057] Comparative Example 2
[0058] Take the toothed spherical alumina carrier Z1 wrapped with polyaniline prepared in Example 1, weigh an appropriate amount of palladium chloride to prepare an aqueous solution according to the Pd content of 0.25wt% in the final catalyst, immerse the carrier Z1 in the palladium chloride solution at 60°C for 4h, then dry at 100°C for 6h, and calcine at 160°C for 4h to obtain catalyst E2. The carbon content in the catalyst was measured, and the catalytic anthraquinone hydrogenation performance of catalyst E2 was evaluated using a fixed bed microreactor under the above experimental conditions, and the results are shown in Table 1.
[0059] Comparative Example 3
[0060] The polyaniline-wrapped toothed spherical alumina carrier Z1 prepared in Example 1 was carbonized at 700°C in a nitrogen atmosphere for 6 hours. Then, based on the Pd content of 0.25 wt% in the final catalyst, the treated carrier was immersed in a palladium chloride solution at 50°C for 5 hours, then dried at 110°C for 5 hours, calcined at 450°C for 3 hours, and reduced at 150°C for 2 hours in a hydrogen atmosphere to obtain catalyst E3. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of catalyst E3 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0061] Comparative Example 4
[0062] A mixed solution of 0.04 mol / L glucose and 0.01 mol / L ammonium molybdate was prepared, 100 g / L toothed spherical alumina balls were added, and the mixture was immersed for 1 hour and then filtered. The mixture was dried at 80 °C for 12 hours, and then carbonized at 800 °C in a nitrogen atmosphere for 3 hours. Then, based on the Pd content of 0.25 wt% in the final catalyst, the treated carrier was immersed in a palladium chloride solution at 60 °C for 3 hours, and then dried at 100 °C for 4 hours to obtain catalyst E4. The carbon content in the catalyst was determined, and the catalytic anthraquinone hydrogenation performance of catalyst E4 was evaluated using a fixed bed microreactor under the above experimental conditions. The results are shown in Table 1.
[0063] Table 1 Anthraquinone hydrogenation results catalyzed by different catalysts
Claims
1. A hydrogenation catalyst, characterized in that: The catalyst uses an inorganic refractory oxide as a carrier, a Group VIIIB noble metal as an active component, and carbon as an additive. The Group VIIIB noble metal active component and the additive carbon are distributed on the surface of the inorganic refractory oxide carrier; Based on the weight of the final hydrogenation catalyst, the content of the Group VIIIB noble metal active component is 0.05% to 2% in terms of single substance, and the content of the additive carbon is 0.2% to 5%; The preparation method of the hydrogenation catalyst comprises the following steps: (1) selecting or preparing a shaped inorganic refractory oxide carrier, and coating the surface of the inorganic refractory oxide carrier with a high molecular polymer; (2) introducing a Group VIIIB noble metal active component into the material obtained in step (1); (3) The material obtained in step (2) is subjected to carbonization treatment to obtain a final hydrogenation catalyst; The high molecular polymer is one or more of polyaniline, polypyrrole and polythiophene; In step (3), the carbonization treatment is performed by calcining under a protective atmosphere, wherein the protective atmosphere is a hydrogen atmosphere or an inert gas atmosphere; the calcining temperature is 400° C. to 1000° C., and the calcining time is 1 h to 24 h.
2. The catalyst according to claim 1, characterized in that: Based on the weight of the final hydrogenation catalyst, the content of the Group VIIIB noble metal active component in terms of single substance is 0.2% to 0.35%, and the content of the additive carbon is 0.2% to 2%.
3. The catalyst according to claim 1, characterized in that: The inorganic refractory oxide is selected from one or more of silicon dioxide, aluminum oxide, zirconium oxide, magnesium oxide, titanium oxide, calcium oxide, silicon aluminum oxide, silicon magnesium oxide, and molecular sieves.
4. The catalyst according to claim 1, characterized in that: The inorganic refractory oxide is selected from alumina and silica.
5. The catalyst according to claim 3, characterized in that: Based on the weight of the final hydrogenation catalyst, the content of the inorganic refractory oxide carrier is 90% to 99.7%.
6. The catalyst according to claim 5, characterized in that: Based on the weight of the final hydrogenation catalyst, the content of the inorganic refractory oxide carrier is 97% to 99%.
7. The catalyst according to claim 1, characterized in that: The Group VIIIB noble metal is selected from at least one of Pd, Rh and Pt.
8. The catalyst according to claim 7, characterized in that: The Group VIIIB noble metal is selected from at least one of Pt and Pd.
9. The catalyst according to claim 1, characterized in that: The catalyst contains other auxiliary components, which are one or more of Fe, Cu, Ni, Zn, B and P.
10. The catalyst according to claim 9, characterized in that: The other additives are distributed on the surface of the inorganic refractory oxide carrier. Based on the weight of the final hydrogenation catalyst, the content of the other additives in terms of single substance is 0.2% to 3%.
11. The catalyst according to claim 10, characterized in that: Based on the weight of the final hydrogenation catalyst, the content of other additives in terms of single substance is 0.5% to 1%.
12. The catalyst according to claim 1, characterized in that: The inorganic refractory oxide carrier is a formed carrier, and the carrier is one of spherical, strip-shaped and clover-shaped.
13. The catalyst according to claim 12, characterized in that: The inorganic refractory oxide carrier is a formed carrier, and the carrier is spherical.
14. The catalyst according to claim 12, characterized in that: The inorganic refractory oxide carrier is a formed carrier, and the carrier is in the shape of a toothed ball.
15. A method for preparing a hydrogenation catalyst according to any one of claims 1 to 14, characterized in that: The steps include: (1) selecting or preparing a shaped inorganic refractory oxide carrier, and coating the surface of the inorganic refractory oxide carrier with a high molecular polymer; (2) introducing a Group VIIIB noble metal active component into the material obtained in step (1); (3) The material obtained in step (2) is subjected to carbonization treatment to obtain a final hydrogenation catalyst; The high molecular polymer is one or more of polyaniline, polypyrrole and polythiophene; In step (3), the carbonization treatment is performed by calcining under a protective atmosphere, wherein the protective atmosphere is a hydrogen atmosphere or an inert gas atmosphere; the calcining temperature is 400° C. to 1000° C., and the calcining time is 1 h to 24 h.
16. The method according to claim 15, characterized in that: In step (1), the inorganic refractory oxide carrier surface-coated high molecular polymer is prepared by a polymerization reaction on the surface of the inorganic refractory oxide carrier.
17. The method according to claim 15, characterized in that: In step (2), the active component of Group VIIIB noble metal is introduced into the material obtained in step (1) by an impregnation method, wherein the impregnation method is equal volume impregnation, excess volume impregnation or spray impregnation, and the pH value of the impregnation solution is controlled between 2.5 and 4.
5.
18. The method according to claim 15, characterized in that: In step (2), other auxiliary components are introduced into the material obtained in step (1), and the other auxiliary components are one or more of Fe, Cu, Ni, Zn, B, and P, and the introduction method is a spray impregnation method.
19. The method according to claim 15, characterized in that: In step (2), after the introduction of the Group VIIIB noble metal active component and / or other auxiliary components, a drying process is included, wherein the drying temperature is 80° C. to 180° C. and the drying time is 8 h to 24 h.
20. The method according to claim 15, characterized in that: In step (3), the carbonization treatment is performed by calcining under a protective atmosphere, and the protective atmosphere is a hydrogen atmosphere.
21. The method according to claim 15, characterized in that: In step (3), the calcination temperature is 600°C to 800°C.
22. The method according to claim 15, characterized in that: In step (3), the calcination time is 3h~8h.
23. The method according to claim 15, characterized in that: In step (3), the protective atmosphere used in the carbonization treatment is a nitrogen atmosphere.
24. Use of the hydrogenation catalyst according to any one of claims 1 to 14 in producing hydrogen peroxide by hydrogenation of anthraquinone.
Citation Information
Patent Citations
Preparation of noble metal catalyst with nanometer sandwich structure and application thereof in direct synthesizing of hydrogen peroxide by hydrogen gas and oxygen gas
CN109806861A
Catalyst for producing hydrogen peroxide by anthraquinone method and preparation method thereof
CN112718012A